Second-order elastoplastic analysis of semirigid steel frames under cyclic loading - Vimonsatit, Vanissorn; Tangaramvong, S.; Tin-Loi, F. (Pergamon, 2012)
The evolutive second-order geometry elastoplastic analysis of flexibly connected planar structures is performed to investigate their cyclic behavior under quasistatic loading conditions. The formulation is cast as a mathematical programming problem, involving so-called ‘‘complementarity’’ constraints. A ‘‘fictitious force’’ concept, that preserves static-kinematic duality, is used to describe geometric nonlinearity. A second-order approximation, deemed sufficiently accurate for practical structures, is adopted. A semirigid connection is idealized as a zero-length elastoplastic element attached to either or both ends of a beam element. Inelasticity is captured through the familiar generalized plastic hinge concept, and a piecewise linear approximation of the nonlinear plastic capacity domain is used to represent the yield condition. A number of examples concerning realistic structures and benchmark cases is provided to check the validity and applicability of the proposed method and to study the cyclic behavior of flexibly connected planar frames.